O Bolsa Família como pretenso modelo brasileiro de bem-estar social - Pistinizi, Bruno Fraga (2019)
The objective of the thesis consists in analyzing the supposed Brazilian model of social welfare. For this, it is necessary to start from the observation of the current condition of capitalism, which chooses for a rational allocation of available human and material resources, with emphasis on metabolic control synthesized by a formal and real subordination of labor, according to Mészáros' critique. For capitalism, it is incompatible for the State to take care of social question, however, when dealing with the reproduction maintenance level, the State assumes responsibility for the social question. In this way, it is now a public task to welcome the new poor who, in the 21st Century, have acquired a condition of misery due to the technological changes of neoliberalism. New expectations and purposes, adapted to the heterogeneous perspectives of life cycles, have altered the contemporary reality of social welfare policies. Changes in the family, occupational and demographic structure affected the adaptation of existing forms or types of social welfare, so that the universality in guaranteeing access to essential public services occurs only with the implementation of specific state policies, focused in the promising emancipation of individuals. The thesis establishes a relationship between the adaptation of social welfare policies and the Bolsa Família (family allowance) Program, established in 2004 and considered a pioneer in the perspective of social policies aimed at the construction of equal opportunities. However, economically oriented social policies face either liberal criticism of offense to the principle of legal reserve, or external pressure of fiscal austerity, resulting in the imposition of restrictions on social rights. The need for consolidation and expansion of the Bolsa Família Program symbolized the essence of the protection of social rights, especially the rescue of the autonomy and dignity of the human person; but the program did not established as model of a social welfare